All-solid waste alkali-activated recycled concrete and preparation method thereof

By constructing a composite cementitious system through the combination of various solid wastes, the problems of setting control and unstable mechanical properties of existing alkali-activated concrete have been solved, realizing the preparation of high-strength, durable and economical all-solid-waste concrete, reducing resource consumption and emissions.

CN120965251AInactive Publication Date: 2025-11-18GUANGZHOU UNIVERSITY +1

Patent Information

Application Number
CN202511501668.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-21
Publication Date
2025-11-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing alkali-activated concrete often relies on a single or a few types of solid waste, making it difficult to control the setting time, prone to early cracking or later strength reduction, with unstable mechanical properties, poor durability, and failing to completely break free from dependence on traditional resources.

Method used

Using a variety of industrial and construction solid wastes such as blast furnace slag, recycled concrete, recycled red brick, phosphogypsum, and iron tailings sand as core components, a CASH gel and ettringite composite cementing system is constructed through precise proportioning. Polycarboxylate superplasticizer and sodium tetraborate decahydrate are used to regulate coagulation, forming a dense structure and providing excellent mechanical and durability properties.

Benefits of technology

It achieves high strength, chemical erosion resistance, and impermeability of all-solid waste concrete, reduces the consumption of natural resources and carbon dioxide emissions, improves the utilization rate of solid waste, and provides excellent construction performance and economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120965251A_ABST
    Figure CN120965251A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to all-solid waste alkali-activated recycled concrete and a preparation method thereof. The concrete is prepared from the following raw materials in parts by weight: 360 to 500 parts of blast furnace slag, 180 to 400 parts of recycled concrete, 90 to 270 parts of recycled red bricks, 40 to 90 parts of silica fume, 30 to 90 parts of phosphogypsum, 240 to 370 parts of iron tailing sand, 350 to 420 parts of recycled concrete coarse aggregate, 200 to 400 parts of alkali activator, 10 to 30 parts of polycarboxylate superplasticizer, 20 to 50 parts of sodium tetraborate decahydrate and 300 to 500 parts of water. According to the invention, through fine proportioning and functional synergy of all the components, a solution of all-solid waste concrete with excellent mechanical properties, durability, construction performance and economical efficiency is provided, and the concrete has a wide application prospect in the fields of green buildings and solid waste recycling.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a full-solid-waste alkali-activated recycled concrete and a preparation method thereof. BACKGROUND

[0002] Ordinary Portland cement concrete (OPCC) is one of the most widely used building materials in current construction projects. However, its production process highly depends on natural resources such as limestone and clay, and needs to go through a "two grinding and one burning" process, consuming a large amount of energy. In addition, according to statistics, about 0.6-1.0 tons of carbon dioxide are emitted per ton of cement produced, and the cement industry contributes 7%-8% of the global carbon dioxide emissions, causing serious burden to the environment.

[0003] In addition, the disposal of construction waste and industrial solid waste also faces severe challenges. For example, a large amount of solid waste such as blast furnace slag, waste concrete, red brick, phosphogypsum, and iron tailings sand is usually treated by open-air storage, which not only occupies land resources, but also has the risk of polluting soil and groundwater. Although some researches have tried to use part of the solid waste to prepare alkali-activated cementitious materials, there are still the following technical defects: the existing alkali-activated concrete mostly depends on a single or a few kinds of solid waste, and the collaborative use of multiple solid wastes is insufficient; the setting time of the traditional alkali-activated system is not easy to control, and early cracking or late strength reversal is easy to occur; the activity of some solid waste is low, resulting in unstable mechanical properties and poor durability of the concrete; and the existing technology often needs to introduce cement or natural aggregate, which cannot completely get rid of the dependence on traditional resources. SUMMARY

[0004] The purpose of the present application is to provide a full-solid-waste alkali-activated recycled concrete and a preparation method thereof to solve the problems in the prior art. Through the fine proportioning and functional synergy of each component, a full-solid-waste concrete solution is provided, which has excellent mechanical properties, durability, construction performance, and economy.

[0005] To achieve the above-mentioned purpose, the present application provides a full-solid-waste alkali-activated recycled concrete, which comprises the following raw materials in parts by weight: blast furnace slag 360-500 parts, recycled concrete 180-400 parts, recycled red brick 90-270 parts, silica fume 40-90 parts, phosphogypsum 30-90 parts, iron tailings sand 240-370 parts, recycled concrete coarse aggregate 350-420 parts, alkali activator 200-400 parts, polycarboxylate superplasticizer 10-30 parts, sodium tetraborate decahydrate 20-50 parts, and water 300-500 parts.

[0006] Preferably, the mass fraction of CaO in the blast furnace slag is 39-40%, the mass fraction of SiO2 is 27-28%, and the mass fraction of Al2O3 is 15-16%; The mass fraction of CaO in the recycled concrete is 15.5-16.5%, the mass fraction of SiO2 is 61-62%, and the mass fraction of Al2O3 is 12-13%; The mass fraction of CaO in the recycled red brick is 6-7%, the mass fraction of SiO2 is 59-60%, and the mass fraction of Al2O3 is 17-18%; The mass fraction of SiO2 in the silica ash is 96-97%. The mass fraction of Ca2SO4 in the phosphogypsum is 95.5-96.5%.

[0007] Preferably, the fineness modulus of the iron tailings sand is 2.3-2.8. The average particle size of the recycled concrete coarse aggregate is 16-25mm.

[0008] Preferably, the alkali activator comprises sodium hydroxide and water glass, and the weight ratio of sodium hydroxide to water glass is 30-70:150-350.

[0009] Preferably, the modulus of the water glass is 3.1-3.5, and the solid content is 35-36%.

[0010] Preferably, the water-reducing rate of the polycarboxylic acid water-reducing agent is greater than or equal to 25%, and the solid content is 35-45%.

[0011] The application further provides a preparation method of the full-solid-waste alkali-activated recycled concrete. The raw materials are mixed, poured, demolded and maintained to obtain the full-solid-waste alkali-activated recycled concrete.

[0012] Preferably, the mixing of the raw materials comprises the following steps: S1. The blast furnace slag, the recycled concrete, the recycled red brick, the silica ash and the phosphogypsum are first mixed to obtain a first mixture; S2. The first mixture, the iron tailings sand and the recycled concrete coarse aggregate are second mixed to obtain a second mixture; S3. The alkali activator, the polycarboxylic acid water-reducing agent, the sodium tetraborate decahydrate and water are third mixed with the second mixture.

[0013] Preferably, the first mixing, the second mixing and the third mixing are performed for 1-5 minutes.

[0014] Preferably, the maintenance is performed at a temperature of 18-22 DEG C and a humidity of greater than or equal to 95%.

[0015] The application has the following beneficial effects: 1.The present application provides a kind of all solid waste alkali excitation recycled concrete, by weight parts, including the following raw materials: blast furnace slag 360-500 parts, recycled concrete 180-400 parts, recycled red brick 90-270 parts, silica fume 40-90 parts, phosphogypsum 30-90 parts, iron tailings sand 240-370 parts, recycled concrete coarse aggregate 350-420 parts, alkali excitation agent 200-400 parts, polycarboxylate superplasticizer 10-30 parts, sodium borate decahydrate 20-50 parts, water 300-500 parts.

[0016] The present application uses blast furnace slag, recycled concrete, recycled red brick, phosphogypsum, iron tailings and other industrial and building solid waste as core components, without relying on traditional cement and natural sandstone. This not only greatly improves the comprehensive utilization rate of bulk solid waste, effectively reduces the land occupation and environmental pollution problems caused by solid waste storage, but also greatly reduces the natural resource consumption, energy consumption and carbon dioxide emissions caused by cement production and stone mining from the source, deeply meets the needs of green low carbon and sustainable development.

[0017] The present application builds a composite cementitious system mainly composed of C-A-S-H gel and supplemented by ettringite (AFt) through fine proportioning and functional synergy of each component. Blast furnace slag rapidly dissociates in a strong alkali environment, forming a large amount of C-A-S-H gel, which contributes mainly to strength and cementing properties; recycled concrete and recycled red brick serve as auxiliary cementitious materials, partially participating in the reaction to generate gel phase, and together with silica fume and unreacted microparticles, they play a "micro-aggregate effect", effectively filling pores and refining pore structure, making the concrete interior more dense. In addition, the sulfate ions provided by phosphogypsum react with active aluminum to form AFt crystals, not only providing additional early strength, but also further optimizing the pore structure. Ultimately, the product of the present application exhibits high mechanical properties and excellent resistance to chemical attack and permeability.

[0018] The present application realizes precise regulation of workability and setting and hardening through compounding of functional admixtures. Polycarboxylate superplasticizer efficiently disperses particles through steric hindrance and electrostatic repulsion effect, releases wrapped water, and still guarantees excellent fluidity at low water-binder ratio. Sodium borate decahydrate as a retarder effectively delays the rapid progress of alkali excitation reaction, avoids rapid loss of workability and early cracking risk, and provides a generous construction window. At the same time, the solid framework composed of iron tailings sand and recycled concrete coarse aggregate, together with the low shrinkage property of the system, ensures excellent volume stability and long-term durability of the concrete.

[0019] 2.The present application also provides a preparation method of all solid waste alkali excitation recycled concrete, comprising the following steps: mixing the raw materials, pouring, demolding and curing after molding to obtain all solid waste alkali excitation recycled concrete.

[0020] The raw material source is wide, and the preparation method is clear, simple and easy to scale production.

[0021] 3. In summary, the application provides a full solid waste concrete solution with excellent mechanical properties, durability, construction performance and economy, which has wide application prospects in green building and solid waste resource utilization. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 is a preparation process schematic diagram of the full solid waste alkali-activated recycled concrete in the application. DETAILED DESCRIPTION

[0023] The application provides a full solid waste alkali-activated recycled concrete, which comprises the following raw materials in parts by weight: blast furnace slag 360-500 parts, recycled concrete 180-400 parts, recycled red brick 90-270 parts, silica ash 40-90 parts, phosphogypsum 30-90 parts, iron tailings sand 240-370 parts, recycled concrete coarse aggregate 350-420 parts, alkali activator 200-400 parts, polycarboxylic acid water reducer 10-30 parts, sodium tetraborate decahydrate 20-50 parts, and water 300-500 parts.

[0024] In the application, the blast furnace slag is a by-product generated in the ironmaking process of a blast furnace in the steel industry; the particle size of the blast furnace slag is 1400-1500 mesh; the mass fraction of CaO in the blast furnace slag is 39-40%, the mass fraction of SiO2 is 27-28%, and the mass fraction of Al2O3 is 15-16%.

[0025] In the application, the process for obtaining the recycled concrete comprises: sequentially subjecting the waste concrete blocks in construction waste to impurity removal, crushing, grinding, and finally passing through a 700-900 mesh sieve by using conventional technical means in the field to obtain the recycled concrete; the mass fraction of CaO in the recycled concrete is 15.5-16.5%, the mass fraction of SiO2 is 61-62%, and the mass fraction of Al2O3 is 12-13%.

[0026] In the application, the process for obtaining the recycled red brick comprises: sequentially subjecting the waste sintered red brick to crushing and grinding by using conventional technical means in the field, and finally passing through a 1100-1300 mesh sieve to obtain the recycled red brick; the mass fraction of CaO in the recycled red brick is 6-7%, the mass fraction of SiO2 is 59-60%, and the mass fraction of Al2O3 is 17-18%.

[0027] In the application, the particle size of the silica ash is 900-1100 mesh; the mass fraction of SiO2 in the silica ash is 96-97%.

[0028] In the application, the phosphogypsum is a by-product of the wet-process phosphoric acid industry; the particle size of the phosphogypsum is 1100-1300 mesh; the mass fraction of Ca2SO4 in the phosphogypsum is 95.5-96.5%.

[0029] In the application, the iron tailings sand is a waste produced in the process of iron ore processing and smelting; the fineness modulus of the iron tailings sand is 2.3-2.8.

[0030] In the application, the recycled concrete coarse aggregate is a particle obtained by crushing and screening the waste concrete; the average particle size of the recycled concrete coarse aggregate is 16-25 mm.

[0031] In the application, the alkali activator includes sodium hydroxide and water glass, and the weight ratio of the sodium hydroxide to the water glass is 30-70:150-350.

[0032] In the application, the modulus of the water glass is 3.1-3.5, and the solid content is 35-36%.

[0033] The solid content refers to the mass fraction of solid substances in the water glass.

[0034] In the application, after the sodium hydroxide and the water glass are mixed, the sodium hydroxide is fully stirred to be completely dissolved, and then the alkali activator is obtained by standing and cooling for 22-26 h.

[0035] In the application, the water-reducing rate of the polycarboxylate superplasticizer is ≥25%, and the solid content is 35-45%.

[0036] The solid content refers to the mass fraction of solid substances in the polycarboxylate superplasticizer.

[0037] The application further provides a preparation method of the full-solid-waste alkali-activated recycled concrete. The raw materials are mixed, poured, demolded and cured to obtain the full-solid-waste alkali-activated recycled concrete.

[0038] In the application, the mixing of the raw materials includes: S1. The blast furnace slag, the recycled concrete, the recycled red brick, the silica fume and the phosphogypsum are first mixed to obtain a first mixture; S2. The first mixture, the iron tailings sand and the recycled concrete coarse aggregate are second mixed to obtain a second mixture; S3. The alkali activator, the polycarboxylate superplasticizer, the sodium tetraborate decahydrate, water and the second mixture are third mixed.

[0039] In the application, in S3, the alkali activator, the polycarboxylate superplasticizer, the sodium tetraborate decahydrate and water are fully mixed, and then the second mixture is third mixed.

[0040] In the present application, the time of the first mixing, the second mixing and the third mixing is 1-5 min respectively.

[0041] In the present application, after mixing the raw materials, pour into the mold, vibration compaction, surface film, 22-26h after demolding for maintenance.

[0042] In the present application, the temperature of the maintenance is 18-22℃, and the humidity is ≥95%.

[0043] The preparation process of the full solid waste alkali activated recycled concrete in the present application is shown in the schematic diagram as shown in the figure. Figure 1

[0044] The present application is further described below in conjunction with examples. Unless otherwise defined, the technical terms or scientific terms used in the present application should be understood as the usual meaning understood by those skilled in the art in the field to which the present application belongs. The features mentioned in the present application or the features mentioned in the specific examples can be combined arbitrarily, and these specific examples are only used to illustrate the present application and not to limit the scope of the present application.

[0045] In the following examples of the present application, the blast furnace slag is a byproduct generated in the process of blast furnace ironmaking in the steel industry, the particle size is 1450 mesh, the mass fraction of CaO in the blast furnace slag is 39.62%, the mass fraction of SiO2 is 27.41%, and the mass fraction of Al2O3 is 15.82%; the process of obtaining the recycled concrete includes: the waste concrete blocks in the construction waste are sequentially subjected to impurity removal, crushing, grinding, and sieving through an 800 mesh screen to obtain; the mass fraction of CaO in the recycled concrete is 16.01%, the mass fraction of SiO2 is 61.74%, and the mass fraction of Al2O3 is 12.53%; the process of obtaining the recycled red brick includes: the waste sintered red brick is sequentially subjected to crushing and grinding, and sieving through a 1200 mesh screen to obtain; the mass fraction of CaO in the recycled red brick is 6.29%, the mass fraction of SiO2 is 59.34%, and the mass fraction of Al2O3 is 17.79%; the particle size of silica fume is 1000 mesh, and the mass fraction of SiO2 in the silica fume is 96.39%; the phosphogypsum is a byproduct of the wet-process phosphoric acid industry, the particle size is 1200 mesh, and the mass fraction of Ca2SO4 in the phosphogypsum is 96.01%; the iron tailings sand is a waste generated in the process of iron ore processing and smelting, and the fineness modulus of the iron tailings sand is 2.5; the recycled concrete coarse aggregate is a particle obtained by crushing and sieving the waste concrete, and the average particle size of the recycled concrete coarse aggregate is 21mm; the modulus of the water glass is 3.3, and the solid content is 35.5%; the water-reducing rate of the polycarboxylic acid water-reducing agent is 27%, and the solid content is 40%.

[0046] Example 1 The present embodiment provides a full solid waste alkali activated recycled concrete, which comprises the following raw materials in parts by weight: ​Blast furnace slag 495 parts, recycled concrete 180 parts, recycled red brick 180 parts, silica fume 45 parts, phosphogypsum 45 parts, iron tailings sand 240 parts, recycled concrete coarse aggregate 360 parts, alkali activator 234 parts, polycarboxylate superplasticizer 10 parts, sodium tetraborate decahydrate 28 parts, water 358 parts.

[0047] The preparation process of the alkali activator includes the following steps: mixing sodium hydroxide and water glass (the weight ratio of sodium hydroxide to water glass is 40:194), fully stirring to dissolve the sodium hydroxide, and then standing and cooling for 24 hours to obtain the alkali activator.

[0048] The embodiment also provides a preparation method of the full-solid-waste alkali-activated recycled concrete. The blast furnace slag, the recycled concrete, the recycled red brick, the silica fume and the phosphogypsum are added into a mixer and stirred for 3 minutes; then the iron tailings sand and the recycled concrete coarse aggregate are continuously stirred for 2 minutes; the alkali activator, the polycarboxylate superplasticizer, the sodium tetraborate decahydrate and the water are fully mixed and added into the mixer for continuous stirring for 3 minutes to obtain a mixture.

[0049] The mixture is poured into a mold, vibrated and compacted, and coated on the surface; after 24 hours, the mold is removed, and the obtained sample is placed into a standard curing box for curing under the condition that the temperature is 20 DEG C and the humidity is 97% until a specified age to obtain the full-solid-waste alkali-activated recycled concrete.

[0050] Example 2 The embodiment provides a full-solid-waste alkali-activated recycled concrete, which is different from the full-solid-waste alkali-activated recycled concrete in the embodiment 1 in that the blast furnace slag is modified to 405 parts and the recycled concrete is modified to 270 parts.

[0051] The embodiment also provides a preparation method of the full-solid-waste alkali-activated recycled concrete.

[0052] Example 3 The embodiment provides a full-solid-waste alkali-activated recycled concrete, which is different from the full-solid-waste alkali-activated recycled concrete in the embodiment 1 in that the blast furnace slag is modified to 450 parts and the phosphogypsum is modified to 90 parts.

[0053] The embodiment also provides a preparation method of the full-solid-waste alkali-activated recycled concrete.

[0054] Example 4 The embodiment provides a full-solid-waste alkali-activated recycled concrete, which is different from the full-solid-waste alkali-activated recycled concrete in the embodiment 1 in that the water is modified to 302 parts.

[0055] The embodiment also provides a preparation method of the full-solid-waste alkali-activated recycled concrete.

[0056] Example 5 The embodiment provides a full solid waste alkali-activated recycled concrete, which is different from the embodiment 1 in that the weight ratio of sodium hydroxide and water glass is modified to 48:244, and water is 340 parts.

[0057] The embodiment also provides a preparation method of the full solid waste alkali-activated recycled concrete.

[0058] Embodiment 6 The embodiment provides a full solid waste alkali-activated recycled concrete, which is different from the embodiment 1 in that the weight ratio of sodium hydroxide and water glass is modified to 56:285, and water is 326 parts.

[0059] The embodiment also provides a preparation method of the full solid waste alkali-activated recycled concrete.

[0060] Comparative example 1 The comparative example provides a full solid waste alkali-activated recycled concrete, which is different from the embodiment 1 in that the silica fume is omitted.

[0061] The comparative example also provides a preparation method of the full solid waste alkali-activated recycled concrete.

[0062] Comparative example 2 The comparative example provides a full solid waste alkali-activated recycled concrete, which is different from the embodiment 1 in that the phosphogypsum is omitted.

[0063] The comparative example also provides a preparation method of the full solid waste alkali-activated recycled concrete.

[0064] Experimental example 1 The full solid waste alkali-activated recycled concrete in the embodiment 1 to the embodiment 6 and the comparative example 1 to the comparative example 2 is respectively subjected to slump, 28-day compressive strength, 28-day flexural strength and dry shrinkage rate tests, wherein the slump test is performed according to GB / T 50080-2016 "Standard Test Methods for Properties of Fresh Ordinary Concrete"; the 28-day compressive strength and the 28-day flexural strength tests are performed according to GB / T 50081-2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete"; and the dry shrinkage rate test is performed according to GB / T 50082-2024 "Standard Test Methods for Long-Term Performance and Durability of Concrete". The test results are recorded in Table 1.

[0065] Table 1 Test results ;

[0066] Therefore, the application adopts the above-mentioned full-solid-waste alkali-activated recycled concrete and the preparation method thereof, through fine matching and function synergy of each component, the final obtained full-solid-waste concrete has excellent mechanical properties, durability, construction performance and economy, and has wide application prospect in the fields of green building and solid waste resource.

[0067] Finally, it should be noted that: the above examples are only used to illustrate the technical solutions of the present application, but not to limit them, although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that: it can still modify or equivalently replace the technical solutions of the present application, and these modifications or equivalent replacements cannot make the modified technical solutions deviate from the spirit and scope of the technical solutions of the present application.

Claims

1. A type of all-solid waste alkali-activated recycled concrete, characterized in that, By weight, it includes the following ingredients: 360-500 parts blast furnace slag, 180-400 parts recycled concrete, 90-270 parts recycled red brick, 40-90 parts silica fume, 30-90 parts phosphogypsum, 240-370 parts iron tailings sand, 350-420 parts recycled concrete coarse aggregate, 200-400 parts alkali activator, 10-30 parts polycarboxylate superplasticizer, 20-50 parts sodium tetraborate decahydrate, and 300-500 parts water.

2. The all-solid waste alkali-activated recycled concrete according to claim 1, characterized in that, The mass fraction of CaO in blast furnace slag is 39-40%, the mass fraction of SiO2 is 27-28%, and the mass fraction of Al2O3 is 15-16%. The mass fraction of CaO in recycled concrete is 15.5-16.5%, the mass fraction of SiO2 is 61-62%, and the mass fraction of Al2O3 is 12-13%. The mass fraction of CaO in recycled red bricks is 6-7%, the mass fraction of SiO2 is 59-60%, and the mass fraction of Al2O3 is 17-18%. The mass fraction of SiO2 in silica fume is 96-97%; The mass fraction of Ca2SO4 in phosphogypsum is 95.5-96.5%.

3. The all-solid waste alkali-activated recycled concrete according to claim 1, characterized in that, The fineness modulus of iron tailings sand is 2.3-2.8; The average particle size of coarse aggregate in recycled concrete is 16-25 mm.

4. The all-solid waste alkali-activated recycled concrete according to claim 1, characterized in that, Alkali activators include sodium hydroxide and water glass, with a weight ratio of sodium hydroxide to water glass of 30-70:150-350.

5. The all-solid waste alkali-activated recycled concrete according to claim 4, characterized in that, The modulus of water glass is 3.1-3.5, and the solid content is 35-36%.

6. The all-solid waste alkali-activated recycled concrete according to claim 1, characterized in that, The water reduction rate of polycarboxylate superplasticizer is ≥25%, and the solid content is 35-45%.

7. The method for preparing all-solid waste alkali-activated recycled concrete according to any one of claims 1-6, characterized in that, Includes the following steps: The raw materials are mixed, poured, and after molding, the formwork is removed and cured to obtain all-solid waste alkali-activated recycled concrete.

8. The method for preparing all-solid waste alkali-activated recycled concrete according to claim 7, characterized in that, Mixing the ingredients includes: S1. Blast furnace slag, recycled concrete, recycled red brick, silica fume, and phosphogypsum are mixed in a first mixture to obtain a first mixture; S2. The first mixture, iron tailings sand, and recycled concrete coarse aggregate are mixed in a second mixture to obtain a second mixture; S3. Mix the alkali activator, polycarboxylate superplasticizer, sodium tetraborate decahydrate, water, and the second mixture in a third mixing.

9. The method for preparing all-solid waste alkali-activated recycled concrete according to claim 8, characterized in that, The mixing times for the first, second, and third mixing are 1-5 minutes, respectively.

10. The method for preparing all-solid waste alkali-activated recycled concrete according to claim 7, characterized in that, The temperature for maintenance is 18-22℃, and the humidity is ≥95%.

Citation Information

Patent Citations

  • Solid waste cementing material, all-solid-waste lightweight concrete and preparation method of all-solid-waste lightweight concrete

    CN114634318A

  • All-solid-waste low-carbon concrete and preparation method thereof

    CN118754522A

  • One-step cement-free concrete and preparation method thereof

    CN120398474A

  • Multi-source solid waste-based low-carbon geopolymer cementing material as well as preparation method and application thereof

    CN120441216A

Cited By

  • Green and harmless solid-waste-based micro-expansive impermeable full-recycled concrete and preparation method thereof

    CN121673013A